Alim - Bahrul Alim; Nurhikmah; Arismunandar (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2023)
This type of research and development aims to identify the need for digital math books, design digital math books, and measure the level of validity, practicality, and effectiveness of digital math books. The digital book development process refers to the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. This research was conducted at SMPN 5 Watansoppeng with the whole research subject to see the effectiveness of digital math books, 2 experts to get the validity of the digital math books developed, learning achievement tests in large group trials to see the effectiveness of digital books, and teacher response questionnaires to see the practicality of digital books. The results of the study show that the validation of material experts is in a good category and that media experts are in a very good category so that digital math books can be used in the learning process. The results of individual and small group trials by distributing questionnaires to each student's responses were in a good category, while in the large group trials by giving pretests and posttests, scores were in a significant category so that scores were obtained in the effective category. Then an analysis of the level of practicality was carried out by giving the value of the teacher's response to the mathematics subject teacher in the very good category so that a value was obtained in the practical category.